Research on the Mechanism of Improving the Quality of Chinese Residents’ Household Financial Asset Allocation - Zhang, Yi; Zhang, Xinyue; Xin, Fengshuang; Zhou, Zejiong (International Journal of Social Sciences and Public Administration, 2023)
In recent years, China’s economy is in the transition stage from high speed growth to high quality development, and the report of the 20th Party Congress puts forward the new concept of "high quality development of finance", while the family, as an important member of China’s financial market, will be conducive to the high quality of China’s social and financial development by improving the quality of its financial asset allocation. Financial inclusion is intended to create a fair and efficient financial market, which plays a positive role in optimizing the allocation of family financial assets. With the continuous updating of financial technology and financial services, inclusive finance can be developed rapidly, this project will use China’s CHFS data to conduct empirical tests, use hierarchical analysis to define indicators from the fairness and efficiency dimensions to construct the Tobit model as well as the advanced model to analyze the enhancement mechanism of China’s residents’ household financial asset allocation, in order to provide some theoretical thinking for the unfair and inefficient allocation of household financial assets at present.